Price-Fixing in the Iron and Steel Industry - Berglund, Abraham (Quarterly Journal of Economics, 1918)
Extraordinary rise of iron and steel prices in 1916 and 1917, 598. — Comparison with conditions of 1899–1900, 601. — Four main problems involved in government regulation, 603. — Price announcement of September, 1917; nature of reductions, 610. — Further announcements, 612. — Prices maintained in January, 1918; slightly revised in March, 615. — Further slight revision in June, 617. — Conclusion, 618.